Impact of Coaching on the Development of Personal and Social Competences among Secondary School Students - Andrés Fernando Avilés-Dávila; María Eugenia Martín Palacio; Cristina Di Giusto Valle (MDPI AG, 2023)
In this study, the impact of school coaching in Spain on the dimensions that comprise the effective personality construct and the development of those dimensions among secondary school students is analyzed. Differences relating to the variables of gender, course year/age, and the state/private sector of each educational center are specified. A longitudinal study employing a quasi-experimental methodology was conducted with a sample of 310 students in attendance at 6 educational centers within the Community of Madrid, Spain; the study cohort comprised 156 (50.3%) male students and 154 (49.7%) female students. The effective personality questionnaire in secondary education was used for the pre- and post-intervention evaluations, as well as to conduct an open survey once the program had ended. The students who attended the six-session intervention expressed high degrees of satisfaction. Despite the brevity of each session (45-60 min), a slight non-significant improvement was observed in the experimental group relative to the control group in the dimensions that were studied (p > 0.05). Regarding gender, the program worked better with male rather than with female students. It was also more effective within state-aided than in state schools.